THE RELATIONSHIP BETWEEN UNDERSTANDING OF FIQH LEARNING MATERIAL AND THE PRACTICE OF PRAYER WORSHIP OF CLASS VII STUDENTS OF MADRASAH TSANAWIYAH, ASY-SYAAKIRIIN ISLAMIC BOARDING SCHOOL, SUNGAI LALA DISTRICT, INDRAGIRI HULU REGENCY - Tuti Alawiyah; Denny Wahyuni; Nur Zakiyah (Tarbiyah Islamiyah: Jurnal Ilmiah Pendidikan Agama Islam, 2026)
Abstract: This study is motivated by students’ low understanding of Fiqh material, especially regarding the procedures of prayer, which affects the less optimal practice of prayer in daily life. This topic is important to study because Fiqh learning plays a strategic role in shaping students’ awareness and skills in performing worship in accordance with Islamic teachings. The purpose of this study is to determine the relationship between students’ understanding of Fiqh learning materials and their practice of prayer among seventh-grade students at MTs Pondok Pesantren Asy-Syaakiriin Indragiri Hulu. This study uses a quantitative approach with a correlational design. The population consists of 44 students, all of whom were selected as the sample using a saturated sampling technique. Data were collected through tests, questionnaires, and documentation, then analyzed using Pearson Product Moment correlation. The results of the hypothesis test show that the rxy value of 0.664 is higher than the r-table at the 5% and 1% significance levels, indicating that Ha is accepted and Ho is rejected. This means there is a significant and strong relationship. These findings highlight the importance of improving students’ understanding of Fiqh to enhance the quality of their prayer practice. Keywords: Understanding Of Fiqh; Fiqh learning; Prayer Practice